The origin of judicial power in role of authority and function to control and supervise The Congress and The Government in the Constitution of the Kingdom of Thailand B.E. 2550: The constitutional Court - โชติช่วง ทวนชัย (Huachiew Chalermprakiet Law Journal, 2014)
Abstract Unavailable